COMPETENCE OF EDUCATORS IN THE QURAN (THEMATIC INTERPRETATION APPROACH) - Rizka Amalia Rahmadhani; Asnil Aidah Ritonga (Universitas Dharmawangsa, 2021)
ABSTRACTEducation in Islam is global acclimatization, which includes authoritative teachings, and the educator is not only an educator but is appropriate acclimatization to Islamic teachings. Students have strong abilities so that they can realize their respective capacities. Then educators are one of the most urgent components in an education system. Because educators are a connecting line to achieve the goals set by students and other related components. educators have muhtasyam degrees. Educators are expected to be good examples and can provide role models for students and can foster and encourage students in achieving their goals.